Nhancing cognitive and psychosocial well-being among visually impaired university students: the impact of content-focused accessible e-learning material - Magiman, Mohamad Maulana; Ismail, Muhd Zulkifli; Nordin, Mohd Norazmi; Mariappan, Uvathi; Elias, Sofia; Razali, Kauthar; Shafie, Amin Al Haadi; Abbas, Mohd Saleh (Pegem Akademi Yayincilik Egitim Danismanlik Hizmetleri Ticaret A.S., 2024)
This mixed-methods study explores the educational and therapeutic benefits of Content-Focused Accessible E-Learning Material (CFAELM) for visually impaired university students. A total of 49 participants with documented visual impairments were recruited from various academic disciplines across STEM, Humanities, and Social Sciences. Utilizing a combination of pre- and postintervention surveys, cognitive assessments (Montreal Cognitive Assessment - MoCA), psychosocial measures (Psychological Well-being Scale and Social Support Questionnaire), and usage logs, this research provides a holistic view of the impact of CFAELM on this demographic. The findings reveal significant improvements in cognitive functioning post-intervention, with mean MoCA scores increasing from 24.3 (±2.1) to 26.8 (±2.5). Psychosocial well-being also showed notable enhancement; Psychological Well-being Scale scores rose from 65.7 (±8.9) to 72.4 (±7.6), and Social Support Questionnaire scores increased from 28.6 (±4.2) to 31.2 (±3.8). Usage data indicated high engagement levels, with participants accessing CFAELM for an average of 5.2 days per week and spending approximately 3.5 hours per day on the material. Feedback from participants overwhelmingly recognized CFAELM as highly accessible (77.6%) and effective (83.7%) in facilitating their learning experiences. These results underscore the crucial role of tailored e-learning materials in enhancing both the cognitive functions and psychosocial well-being of visually impaired university students. By highlighting significant improvements in academic and psychosocial domains, this study contributes to the discourse on inclusive education, advocating for the integration of accessible e-learning resources in higher education curriculums to better support students with visual impairments. The study's mixed-methods approach further enriches our understanding, offering both quantitative evidence of CFAELM's benefits and qualitative insights into participants' experiences, thus providing a comprehensive overview of its efficacy in meeting the unique educational needs of visually impaired learners.